Indirect Multicultural Experiences: A Multidimensional Journey to Inspire Self-Change - Jun Zhang; Guanglan Rong; Wenxi Du; Yan Bao (Behavioral Sciences)
Self-change is crucial for driving both individual growth and societal progress. Based on schema theory, this study proposes that indirect multicultural experiences may be an effective pathway to promote self-change, with positive emotions and meaning seeking serving as mediators, and social class as a moderator. To test this hypothesis, an online survey was conducted with 1627 participants aged 18–55 years, using scales to assess indirect multicultural experiences, self-change, positive emotions, meaning seeking, and both subjective and objective social classes. The results indicated that indirect multicultural experiences promote self-change not only by enhancing positive emotions but also by fostering meaning seeking. Additionally, social class moderated the relationship between indirect multicultural experiences and self-change, with subjective social class playing a more pronounced role than objective social class. Individuals with higher subjective social class overall benefited more from indirect multicultural experiences. These findings enhance our understanding of the mechanisms behind self-change and suggest that interventions aiming to foster personal growth and self-improvement can benefit from encouraging diverse cultural exposures, focusing on enhancing individuals’ subjective sense of social class.